Breakup Grief - the Difference Between Initiator and Non-initiator Depending on Coping Strategy and Attachment - Ranđelović, Kristina Ž.; Goljović, Nikola R. (Collection of Papers of the Faculty of Philosophy in Priština, 2020)
The aim of this paper is to examine the difference in the intensity of the breakup distress between the initiator and the non-initiator, as well as whether this difference is moderated by coping strategies and inner working models according to the attachment theory. The sample used in the research is convenient and consists of 387 respondents. The age range is between 18-40 (M=23.90; SD=4.22). We used the Close Relationship Experience Questionnaire (Brenan, Clark, & Shaver, 1995), the Brief COPE (Carver, 1997) and the Breakup Distress Scale (Field & al., 2010). The t-test was performed for the independent samples to test the difference between the breakup initiators and non-initiators in the variable of grief after a breakup (t(365)=4.62; p
Keywords: breakup grief; romantic relationships; initiator of break up; coping strategy; attachment